GONDANG DAN SISTEM KEKERABATAN ETNIK ANGKOLA - LIDIA EPANGELIA (Grenek: Jurnal Seni Musik, 2018)
This study aims to find out the Angkola ethnic kinship system, to know Angkolagondang shape and to interpret the relationship of gondang and the ethnickinship system of Angkola. This research is based on a theoretical explainingthe understanding of gondang and the Angkola ethnic kinship system by usingthe theory of deconstruction, semiotics and ethnomusicology. This researchwas conducted from September 2017 to October 2017 in Kecamatan Arse,Simangambat Street, KM. 11, Arse Nauli. The research method used isdescriptive qualitative. The population in the study was non-existent and theresearch sample consisted of five indigenous figures and Angkola artists. Theresearch result explores that gondang and relatives of ethnic Angkola areneeded in showing their identity as ancestral cultural heritage which deservesto be appreciated by society. The relationship between gondang and the ethnickinship system of Angkola states that gondang is a representation of the kinshipsystem by looking at the relationship between each instrument in Angkolagondang ensemble which is a manifestation of na tolu transition in traditionalceremony.